MANAJEMEN BENGKEL MESIN KAPAL PERIKANAN DI KOTA DUMAI - Yoki Jiliansyah; Muchtar Ahmad (Berkala Perikanan Terubuk, 2011)
In order to find out the condition of fishery ship machine workshopmanagement, problems and solutions, so as developing workshop management,survey had been held in three workshops in Dumai city on Juli 2007. Informationand data are collected through interviews with fishery ship machine workshopowner, fishermen, worker and related person in this field. SWOT analysis andfinancial analysis are applied to digest the data as project evaluation to drawdecision about its devolopment strategy.Workshop is a room building which is needed to carn a product includingmechanical activities and fixing ship body parts. Workshop is functioned as aplace to repair the ship machine. In the fishery ship machine workshop in Dumaicity, some already have enough supporting equipment. However, a goodworkshop is a workshop which owns a complete tools and specialized technicianto handle the ship repairment.Based on the SWOT analysis of fishery ship machine workshop in Dumaiwhich is in coordinate I, it can be develoved with the strategy of gasping theopportunity available aggressively and expansively by using the power provided.Meanwhile the financial analysis in 20 % discount factor for 20 years calculationcan be reached NPV, BCR, IRR and PPC that can be beneficial from the threefishery ship machine workshops in Dumai. Finally, the work of fishery shipmachine workshop is deserve to be continued and should be develoved, yet thebusiness license matter and the workshop services should be managed well infuture.